A Low-Cost Easy-Operation Hexapod Walking Machine - Giuseppe Carbone; Marco Ceccarelli (International Journal of Advanced Robotic Systems, 2008)
This paper presents the mechanical design of an hybrid hexapod walking machine that has been designed and built at LARM: Laboratory of Robotics and Mechatronics in Cassino. Basic characteristics are investigated in order to design a leg system with suitable low-cost modular components. Moreover, special care has been addressed in proposing an architecture that can be easily operated by a PLC with on-off logic. Experimental tests are reported in order to show feasibility and operational capability of proposed design.